The Influence of Brand Ambassador, Quality Perception, and Digital Marketing on Purchasing Decisions with Brand Image as a Mediator - Sari, Ni Luh Kade Dwi Purnama; Luh Putu Mahyuni (Amkop Management Accounting Review (AMAR), 2025)
The dissemination of information through today's technology can spread culture and information globally. One of them is Korean culture, also known as Hallyu or Korean Wave. This phenomenon has also become a trend in marketing strategies by using South Korean K-pop idols as brand ambassadors. One of them is Dream NCT (Neo Culture Technology), which is currently developing to attract customers. This study will analyze how K-pop can make a significant contribution to branding among Generation Z. This study attempts to examine the phenomenon of consumer purchasing mediated by brand image. The sample size for this study was 100 Generation Z individuals. Data collection was conducted by distributing questionnaires using Google Forms. The data analysis technique used the SEM-PLS method. This study shows that Brand Ambassador, Quality Perception, and Digital Marketing have a positive and significant effect on Brand Image. This study also found that Brand Image has a positive and significant effect on Purchase Decision. Brand Ambassador, Quality Perception, and Digital Marketing have a positive and significant effect on Purchase Decision through Brand Image.